The Implementation of Literature Circles on Students’ Reading Comprehension of Analytical Exposition Texts - Fitri, Mainar; Fitria, Nurul; Nurzena, Nurzena (Journal of English and Arabic Language Teaching, 2024)
Literature Circles have been found to have effects on students’ reading comprehension.  The question is how Literature Circle can affect students’ reading comprehension in analytical exposition text. This research aimed to examine whether or not there is a significant difference on reading comprehension of analytical exposition texts between students who were taught by using Literature Circles and without using Literature Circles. The research design used in this research was a quasi-experimental design. The researcher used a two-group pre-test and post- test design. The population of this research were the eleventh grade students of Madrasah Aliyah Negeri (Islamic Senior High School)  Pekanbaru., Riau province, Indonesia. The samples of the research were 37 students taken by using Purposive sampling technique.  In collecting the data, researchers used Pre-test and Post-test of reading comprehension of analytical exposition texts in the form of a multiple-choice test. To analyze the data, researchers used an independent sample T-test and eta-squared. The result of the research showed that there was a significant difference on reading comprehension of analytical exposition texts between students taught by using Literature Circles and without using Literature Circles with sigma 2 tailed 0,000. So, it showed that there was an effect of Literature Circles on students’ reading comprehension of analytical exposition texts. The effect size was categorized into large effect (0.26). In conclusion, Literature Circles are effective to help students in reading comprehension of analytical exposition texts. So, it is recommended that teachers should use Literature circles in teaching reading comprehension.